INTENTION TO VISIT MALAYSIAN YOUTH TRAVELER (CASE STUDY: CILETUH PALABUHANRATU UNESCO GLOBAL GEOPARK) - Raden Muhammad Goumelar; Herry Hudrasyah (International Journal of Accounting, Finance and Business, 2021)
UNESCO Palabuhanratu global geopark or it can be abbreviated as CPUGG. It is an international standard geological, biological, and cultural tourist location located in the Sukabumi area of West Java. With the name UNESCO as the name of the organization that oversees the existence of Ciletuh Palabuhanratu, it is hoped that this can attract International Travelers to come to CPUGG which will have an economic impact on the surrounding area. CPUGG has a problem with the very small portion of foreign tourists. So there is a need for research on their intentions to visit tourist attractions. In this study, quantitative research was used to determine the regression relationship between motivation and intention to visit tourist attractions.